Historical epidemiology of hepatitis C virus (HCV) in selected countries. (May 2014) - Bruggmann, P.; Berg, T.; Øvrehus, A. L. H.; Moreno, C.; Brandão Mello, C. E.; Roudot‐Thoraval, F.; Marinho, R. T.; Sherman, M.; Ryder, S. D.; Sperl, J.; Akarca, U.; Balık, İ. and Bihl, F. and Bilodeau, M. and Blasco, A. J. and Buti, M. and Calinas, F. and Calleja, J. L. and Cheinquer, H. and Christensen, P. B. and Clausen, M. and Coelho, H. S. M. and Cornberg, M. and Cramp, M. E. and Dore, G. J. and Doss, W. and Duberg, A. S. and El‐Sayed, M. H. and Ergör, G. and Esmat, G. and Estes, C. and Falconer, K. and Félix, J. and Ferraz, M. L. G. and Ferreira, P. R. and Frankova, S. and García‐Samaniego, J. and Gerstoft, J. and Giria, J. A. and Gonçales, F. L. and Gower, E. and Gschwantler, M. and Guimarães Pessôa, M. and Hézode, C. and Hofer, H. and Husa, P. and Idilman, R. and Kåberg, M. and Kaita, K. D. E. and Kautz, A. and Kaymakoglu, S. and Krajden, M. and Krarup, H. and Laleman, W. and Lavanchy, D. and Lázaro, P. and Marotta, P. and Mauss, S. and Mendes Correa, M. C. and Müllhaupt, B. and Myers, R. P. and Negro, F. and Nemecek, V. and Örmeci, N. and Parkes, J. and Peltekian, K. M. and Ramji, A. and Razavi, H. and Reis, N. and Roberts, S. K. and Rosenberg, W. M. and Sarmento‐Castro, R. and Sarrazin, C. and Semela, D. and Shiha, G. E. and Sievert, W. and Stärkel, P. and Stauber, R. E. and Thompson, A. J. and Urbanek, P. and van Thiel, I. and Van Vlierberghe, H. and Vandijck, D. and Vogel, W. and Waked, I. and Wedemeyer, H. and Weis, N. and Wiegand, J. and Yosry, A. and Zekry, A. and Van Damme, P. and Aleman, S. and Hindman, S. J.
Summary: Chronic infection with hepatitis C virus (HCV) is a leading indicator for liver disease. New treatment options are becoming available, and there is a need to characterize the epidemiology and disease burden of HCV. Data for prevalence, viremia, genotype, diagnosis and treatment were obtained through literature searches and expert consensus for 16 countries. For some countries, data from centralized registries were used to estimate diagnosis and treatment rates. Data for the number of liver transplants and the proportion attributable to HCV were obtained from centralized databases. Viremic prevalence estimates varied widely between countries, ranging from 0.3% in Austria, England and Germany to 8.5% in Egypt. The largest viremic populations were in Egypt, with 6 358 000 cases in 2008 and Brazil with 2 106 000 cases in 2007. The age distribution of cases differed between countries. In most countries, prevalence rates were higher among males, reflecting higher rates of injection drug use. Diagnosis, treatment and transplant levels also differed considerably between countries. Reliable estimates characterizing HCV‐infected populations are critical for addressing HCV‐related morbidity and mortality. There is a need to quantify the burden of chronic HCV infection at the national level.